Two-stage rumenostomy in buffaloes - Maia Teixeira, Pedro Paulo [UNESP]; Machado Silva, Marco Augusto; Viana, Rinaldo Batista (Univ Fed Rio Grande Do Sul, 2014)
Background: Rumenostomy may be performed for therapeutic and digestibility research purposes in bovines, small ruminants and camelids. Several studies requires romenostomy in buffaloes in order to sample ruminal content for laboratorial assays. However, complications and outcome of rumenostomy was poorly studied in buffaloes. Therefore, the aim of the current study was to describe a two-stage rumenostomy technique in buffaloes, focused on intra and post-operative period.Materials, Methods & Results: Nine Murrah buffaloes were submitted to a 36-h and 12-h of food and water fastening. The animals were given acepromazine and maintained in standing position. Flank local anesthesia was carried out. A circular skin incision was carried out in the center of the left flank, followed by divulsion of the external and internal obliques and transversus abdominus muscles, and incision of the peritoneum. Subsequently, a segment of the dorsal aspect of the rumen was grasped and pulled through the flank incision. The rumen was attached to the peritoneum and skin incision margins in four points (dorsal, ventral, cranial and caudal). Additional simple interrupted sutures attaching the rumen serosa to the skin were applied subsequently. Four additional interrupted horizontal mattress sutures were applied equidistantly, taking bites only in the skin and rumen serosa. Following 12 h, the second stage was carried out. The buffaloes were prepared and restrained as performed for the first stage. A circular flap was excised from the exteriorized rumen and the silicone romenostomy cannula was placed. Clinical parameters, postoperative recovery, weight and behavioral pain scale were assessed. Positioning and anesthesia regimen were adequate for the achievement of the procedure. However, two animals fell in the restraint chute during the first surgical stage. Mild ischemia of the exteriorized rumen segment was observed on the second surgical stage, which resulted in less hemorrhage and enhanced cannula positioning. Complete cicatrization and permanent adhesion of the rumen to the skin were achieved. No ruminal leakage to the abdominal cavity occurred. No signs of pain were reported. There were few cases of laxity of the romenostomy opening leading to drop of cannula, myiasis on the margin of the stoma site and few cases of mild ruminal content leakage on the long-term assessment.Discussion: Restraint in standing position was considered adequate, although lateral recumbence constitutes another option. However, higher risk of contamination and technical difficulties in placing the cannulas are expected if lateral recumbence is considered. In other trials using acepromazine, no accidental recumbence occurred. Xylazine was also indicated for chemical restraint of buffaloes. It is known that flexible cannulas provide better anatomic adjustment and adaptation as well as being effective for sampling ruminal content, as seen in the current study. Ruminal leakage is one of the most frequent complications of romenostomy, which may affect animal's welfare. The animals in the current study presented no variations on the body score, even though on those presenting cannula loosening or ruminal content leakage. Moreover, no significant changes of the ruminal content parameters were noticed. Myiasis was also reported following ruminal surgical interventions, which were mainly attributed to extensive breeding. Loss of the cannula, subcutaneous emphysema and suture dehiscence are common complications of romenostomy. Nonetheless, none of those complications were found on the current study. Thus, romenostomy was feasible and efficient for sampling and performing assays of the ruminal content in buffaloes.
Keywords: rumen cannulation; Bubalus bubalis; ruminal stoma; surgery